2022
DOI: 10.2147/ijgm.s382331
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute Effect of SARS-CoV-2 Infection on the Cardiac Autonomic Function

Abstract: Background Recent studies reported a long-lasting effect of COVID-19 infection that extends beyond the active disease and disrupts various body systems besides the respiratory system. The current study aims to investigate the post-acute effect of SARS-CoV-2 infection on cardiovascular autonomic activity, reactivity and sensitivity in patients who had the infection at least 3 months before. Methods This was a comparative cross-sectional observational study. Fifty-nine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
2
3
0
1
Order By: Relevance
“…Taken together, these ndings indicate a normal sympathetic modulation of the heart within 6 months in patients with PCS. These ndings are in line with the observations from Salem et al 23 , who investigated the post-acute effect of SARSCoV-2 infection on cardiovascular autonomic activity, reactivity, and sensitivity, in patients who had the infection at least 3 months before. These authors observed that these patients displayed several parameters of HRV without signi cant changes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, these ndings indicate a normal sympathetic modulation of the heart within 6 months in patients with PCS. These ndings are in line with the observations from Salem et al 23 , who investigated the post-acute effect of SARSCoV-2 infection on cardiovascular autonomic activity, reactivity, and sensitivity, in patients who had the infection at least 3 months before. These authors observed that these patients displayed several parameters of HRV without signi cant changes.…”
Section: Discussionsupporting
confidence: 91%
“…Asarcikli et al 4 have also found an LF/HF ratio increase, which is consistent with sympathetic overactivity. On the other hand, when Salem et al 23 investigated the post-acute effect of SARSCoV-2 infection on cardiovascular autonomic activity in patients with PCS, who were exposed to the infection at least 3 months before, they concluded that despite several parameters of HRV being numerically reduced in these patients with PCS, they were not statistically signi cant.…”
Section: Discussionmentioning
confidence: 97%
“…Dentre os danos cardíacos e vasculares encontrados em pacientes pós COVID-19, destacam-se: isquemia miocárdica, infarto, miocardite e arritmias cardíacas. (Salem et al, 2022). Os sintomas cardiovasculares mais comuns são: dor no peito, palpitação, taquicardia e intolerância ortostática (Yong, 2021).…”
Section: Resultsunclassified
“…One reason could be a longer duration between HRV assessment and COVID-19 infection, as noted in an earlier study. [ 10 ] Another reason could be the non-severe nature of previous COVID-19 infections.…”
Section: Discussionmentioning
confidence: 99%